Difficulties of field training among university students during the COVID-19 pandemic - Haitham Abu Zaid; Mohammad Omar Al-Momani; Hanaa Mustafa Danaa; Karimah Suleiman Aljedayah; Lubna Mahmoud Obeidat; Marleen Mansour AlFalah (Institute of Advanced Engineering and Science, 2023)
This study aimed to uncover the difficulties that special education students face in field training at Al-Balqa Applied University during the corona pandemic. The study investigated whether these difficulties were affected by gender (males-females). To achieve the objectives of the study, the researcher designed survey consisting of 36 items. The sample of the study consisted of 30 male and female students enrolled in the field training course in the first semester of the academic year 2020/22021. The results showed that field training difficulties associated with the subscale of the students and supervisors were high. However, the difficulties related to the training center were medium. The study also showed no statistically significant differences in the difficulties between students due to the gender variable.